AD3W: An educational simulator for instruction-level data dependency analysis - Roque, Alexandre S.; Schievelbein, Guilherme; Losekann, Maikel; Silva, Denilson Rodrigues da (International Journal of Computer Architecture Education, 2013)
This article presents a simulator for instruction-level dependency analysis, aiming to educationally illustrate the possibilities of parallelism in a program. The control algorithm uses conditional branch detection and writes to registers (WAR, WAW, and RAW) as techniques to analyze instruction-level dependencies. The results obtained highlight the reduction in exercise completion and correction times in the classroom, in addition to the practical perception that the simulator helps students understand the concepts related to instruction-level parallelism.